"Managing uncertainty": Experiences of family members of burn patients from injury occurrence to the end-of-life period. Issue 7 (November 2021) - Bayuo, Jonathan; Bristowe, Katherine; Harding, Richard; Agbeko, Anita Eseenam; Baffour, Prince Kyei; Agyei, Frank Bediako; Wong, Frances Kam Yuet; Allotey, Gabriel; Agbenorku, Pius; Hoyte-Williams, Paa Ekow
Highlights: Grief and uncertainty which occur following the injury heighten at the end of life. Family members witness and feel being a part of the patient's suffering. Practice recommendations should include communication, bereavement, and post-bereavement support. Abstract: Background: Although mortality rates associated with burns have decreased, there is still a significant number of persons who may not survive severe forms of the injury and thus, undergo comfort/end of life care. The experiences of family members of persons whose injuries are deemed unsurvivable remain minimally explored and there is a general lack of practice guidelines and recommendations to support them at the end-of-life period. Aim: To explore the experiences of family members whose relatives died in the burn unit to inform the development of practice recommendations. Methods: Qualitative description was employed for this study. Convenience sampling was used to recruit 23 family members of injured persons who died in the burn unit. Face to face semi-structured interviews were conducted and followed up with telephone interviews. The interviews were audio-recorded, transcribed verbatim and thematic analysis performed inductively. Results: Three themes emerged: reactions following injury occurrence, navigating through the experience, and managing uncertainties about survival. The sudden nature of the injury led to feelings of self-blame, guilt, helplessness, and grief and these escalated at the end of life. As the family members journeyed through their uncertainties regarding the outcomes of care, they had a feeling of being a part of the patient's suffering. Family members received little professional support in coming to terms with their loss in the post-bereavement period. Conclusions: Family members experience distress following the occurrence of burns and at the endof-life period. Practice recommendations should focus on communication, bereavement, and post-bereavement support.